2008
DOI: 10.1016/s0377-1237(08)80011-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Recovery after Sevoflurane versus Halothane Anaesthesia in Adult Patients

Abstract: Background: Induction and maintenance characteristics of sevoflurane and halothane have been studied, but little work has been done to compare the postoperative recovery of these two agents. Methods: Sixty adult, ASA I and II patients were allocated randomly into Group A and Group B of 30 each. Group A received sevoflurane and Group B received halothane for maintenance. At the end of surgery early recovery, intermediate recovery and discharge criteria were assessed. Results: Early recovery assessed with the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…[ 20 ] It is again used in many studies for assessing postoperative cognitive recovery. [ 21 22 23 ] Our results were in agreement with those of Dashfield et al . [ 23 ] where there was no significant difference in the P-deletion scores between the two groups, that is, VCI with sevoflurane and IV induction with propofol.…”
Section: Discussionsupporting
confidence: 93%
“…[ 20 ] It is again used in many studies for assessing postoperative cognitive recovery. [ 21 22 23 ] Our results were in agreement with those of Dashfield et al . [ 23 ] where there was no significant difference in the P-deletion scores between the two groups, that is, VCI with sevoflurane and IV induction with propofol.…”
Section: Discussionsupporting
confidence: 93%
“…Another study has considered postoperative agitation as an abnormal and scary behavior (18). Postoperative agitation is commonly performing for preschool children after receiving inhalation anesthetic agents such as sevoflurane (19), desflurane (20), and isoflurane (21,22). In the present study, hemodynamic parameters were evaluated, and no difference in systolic pressure, diastolic pressure, and arterial oxygen saturation was observed, but heart rate was significantly decreased in the T group (P = 0.01).…”
Section: Discussionmentioning
confidence: 56%
“…Sevoflurane, an inhaled anesthetic often used in children, is associated with rapid induction and emergence; its blood solubility is low and there is no airway stimulation. However, sevoflurane has been associated with various complications, including agitation on emergence, [1,18,24] particularly after pediatric ophthalmic surgery (the eyes are covered postoperatively). One study found that 44% of pediatric patients who underwent strabismus surgery showed emergence agitation.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid recovery from sevoflurane anesthesia reduces the risks of coughing and respiratory complications. [1] However, a high incidence of agitation on emergence from anesthesia (50%–80%) has been reported in children who receive sevoflurane. [2] Postoperative agitation not only causes pain and delays discharge from the recovery room, but also requires medical treatment.…”
Section: Introductionmentioning
confidence: 99%